Effect of high and low energy based concentrate diet supplementation on nutrient intake and body weight changes of buffalo bull calves at Subornochar Upozila of Noakhali district in Bangladesh (Bangladesh Journal of Animal Science, 2021)
This study was designed to investigate the effects of supplementation of high and low energy based concentrate diets (13.77 Vs 12.14 MJ/kg DM metabolizable energy) on the nutrient intake and body weight changes of indigenous growing buffalo bull calves in Bangladesh. The crude protein contents of both the supplemented diets were similar (about 12.50% on DM basis). In this study, a total of fifteen indigenous growing buffalo bull calves (av. Live weight 85.10±0.874 kg) were selected from different villages. It was found that the total dry matter intake was the highest (28.22±0.015 g/kg W0.75/d) in group supplemented with high energy concentrate diet along with farmer’s practices (D1), thereafter, in group supplemented with low energy concentrate diet along with farmer’s practices (D2) (27.79±0.015 g/kg W0.75/d) and the lowest (26.39±0.016 g/kg W0.75/d) in control group (D0) in which the animals were fed only farmers practices diet. Similarly, the crude protein intake was the highest in D1 group (2.86 ±0.029 g/kg W0.75/d), followed by D2 group (2.83±0.010 g/kg W0.75/d) and the lowest in farmer’s practices diet, D0 (2.08b±0.021 g/kg W0.75/d).  However, the final body weight of buffalo bull calves was higher in both groups supplemented with concentrate diets (D1 and D2) compared with control (D0) and differed significantly (p0.05) found between D1 and D2 where high energy concentrate supplementation group buffalo bull claves, D1 tended to be higher than low energy concentrate supplementation group buffalo bull claves, D2. The highest final (254.6 kg) body weight was recorded in high energy concentrate supplemented diets and the lowest (144.0 kg) was found in control. Additionally, the average final body weight was increased by 153.40 kg (151.58%), 150.40 kg (152.22%) and 45.60 kg (46.34%) in D1, D2 and D0 group buffalo bull calves, respectively. On the other hand, the average final body weight of D1 and D2 was increased by 110.60 kg (76.80%) and 105.20 kg (73.05%), respectively, compared with D0. In addition, the highest (6.46) feed conversion efficiency (FCE) was recorded in D1 followed by D2 (6.64) and the lowest (12.17) was found in D0. The trends of cost benefit ratio was the same like other considering factors, the highest (1:3.60) found in D1 followed by D2 (1:3.51) and the lowest (1:1.97) in D0. Finally, considering all the parameters, it was clearly indicated that supplementation of concentrate diet along with farmers practice is essential for fast growing, higher body weight gain and more benefits by rearing buffalo bull calves at Subornochar Upozila of Noakhali district in Bangladesh.Bang. J. Anim. Sci. 2021. 50 (1):50-56